2021
DOI: 10.1093/plcell/koab281
|View full text |Cite
|
Sign up to set email alerts
|

Cis-regulatory sequences in plants: Their importance, discovery, and future challenges

Abstract: The identification and characterization of cis-regulatory DNA sequences and how they function to coordinate responses to developmental and environmental cues is of paramount importance to plant biology. Key to these regulatory processes are cis-regulatory modules (CRMs), which include enhancers and silencers. Despite the extraordinary advances in high-quality sequence assemblies and genome annotations, the identification and understanding of CRMs, and how they regulate gene expression, lag significantly behind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
156
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(160 citation statements)
references
References 290 publications
(614 reference statements)
4
156
0
Order By: Relevance
“…The importance of exclusivity of these transcripts in fiber tissue needs to be explored further; however, tissue-specific variants have been shown to regulate the flowering at different developmental stages in Arabidopsis ( Rosloski et al, 2013 ; Ghelli et al, 2018 ). The tissue-specific expression of variants may be due to the presence of tissue-specific promoter architecture, which requires a tightly regulated transcriptional machinery ( Srivastava et al, 2018 ; Das and Bansal, 2019 ; Schmitz et al, 2021 ). During the domestication of cultivated cotton species, these transcripts might be positively selected in modern cotton for fiber-specific features ( Figures 6A,B ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of exclusivity of these transcripts in fiber tissue needs to be explored further; however, tissue-specific variants have been shown to regulate the flowering at different developmental stages in Arabidopsis ( Rosloski et al, 2013 ; Ghelli et al, 2018 ). The tissue-specific expression of variants may be due to the presence of tissue-specific promoter architecture, which requires a tightly regulated transcriptional machinery ( Srivastava et al, 2018 ; Das and Bansal, 2019 ; Schmitz et al, 2021 ). During the domestication of cultivated cotton species, these transcripts might be positively selected in modern cotton for fiber-specific features ( Figures 6A,B ).…”
Section: Discussionmentioning
confidence: 99%
“…One gene pair ( PtHXK2 and 6 ) was speculated to undergo a segmental duplication combined with the sequence analyses, suggesting notable physiological roles associated with evolved mechanisms to adapt to stress stimuli ( Figure 2 a). The cis -regulatory elements predicted in promoter regions indicated the dynamic regulation and evolution of specific gene expression upon various environmental cues [ 53 ]. Therefore, the deduction of principal diverse cis -regulatory elements related to phytohormone response (ABA, GA, MeJA, and Auxin) and stress factors (e.g., MBS, TC-rich, and LRT), along with TF binding sites, provided a hint that the molecular regulation of PtHXKs depends significantly on the crosstalk between phytohormone and glucose signaling pathways [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that these cis ‐regulatory elements do not have the same accessibility for CRL1. The accessibility of cis ‐regulatory elements for a transcription factor in planta can be modulated by chromatin structure, DNA methylation, or the interaction with another protein in its near vicinity (Schmitz et al., 2022). Nevertheless, our data revealed that OsROP and OsbHLH044 constitute direct CRL1 target genes in rice stem bases.…”
Section: Discussionmentioning
confidence: 99%